Evaluation of an environmental education program using a cross-sectoral approach to promote the sustainable use of domestic drains - Martín-Jaime, Juan Jesús; Velasco-Martínez, Leticia Concepción; Tójar-Hurtado, Juan Carlos (MDPI, 2021)
The discharge of hygienic waste down domestic drains has become a socio-environmental problem that is causing serious damage to aquatic ecosystems and wastewater management systems. In this paper, we report the results of our study to determine the effectiveness of an environmental education (EE) program to raise awareness of this problem among primary school students. A longitudinal study was carried out using a survey methodology. A questionnaire, including Likert-scale items, was designed (n = 4362). A study of the reliability and validity of the measure was carried out using validations conducted by experts, Cronbach’s Alpha coefficient, factor analysis, and the categorical analysis of principal components (CATPCA). The analyses showed that there were significant differences between the educational cycles of primary education and two different versions of the program. For example, a second version of the EA program, with a more positive approach, produced an improvement in the acquisition of knowledge, behaviors, and attitudes regarding the development of good habits concerning the use of household drains. The conclusions show the suitability of this cross-sectoral EE program for actively involving students and their families in the proper management of household hygienic waste.
Keywords: Educacion ambiental; Aquatic ecosystems; Environmental education; Values; Pro-environmental behaviour; Hygienic waste